Perlindungan Konsumen Akibat Maraknya Pembangunan Toko Swalayan di Kabupaten Gianyar - Ni Made Isadhanti Nawangsari; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2024)
The rise of the construction of supermarkets in Gianyar Regency causes the competitiveness of business actors to be increasingly fierce and the community as consumers who are not sensitive to their own rights, the position of consumers is getting weaker than business actors. The formulation of this research problem includes: What is the form of legal protection for consumers who make transactions at convenience stores in Gianyar Regency? and What are the legal consequences for convenience store businesses that violate consumer rights? This study is carried out using empirical legal research methodology, which involves investigating how the application of law in society and seeing the law in its practical application. The results of this study explain that consumers receive direct legal protection fromConsumer Protection Act. Consumers who are harmed by the convenience store in the form of damage or goods that have expired are held accountable in the form of direct compensation by the convenience store.